PENGARUH MOTIVASI WAJIB PAJAK, EDUKASI PAJAK, DAN SIFAT MACHIAVELLIAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PREFERENSI RISIKO SEBAGAI VARIABEL MODERASI - Djuniar, Lis; Betri, Betri; Sabrina, Nina; Sari, Dewi Puspa; Melhanu, Sandy Pradana (Universitas Muhammadiyah Palembang, 2024)
This research aims to determine the influence of taxpayer motivation, tax education, and Machiavellian nature on taxpayer compliance with risk preferences as a moderating variable in the service area of the West Ilir Pratama Tax Service Office, Palembang City. The sample used was simple random sampling and could only be used as many as 114 questionnaires from 400 respondents. The data used is primary data. The data collection technique was carried out by distributing questionnaires. The results of this research show that taxpayer motivation, tax education, and Machiavellian traits jointly influence taxpayer compliance. Partially, taxpayer motivation and Machiavellian nature influence taxpayer compliance, while tax education has no influence on taxpayer compliance. MRA hypothesis testing shows that risk preference results are unable to moderate the influence of taxpayer motivation on taxpayer compliance, the influence of tax education on taxpayer compliance, and the influence of Machiavellian traits on taxpayer compliance. Risk preference is only a moderator predictor in the relationship models formed.